1998
DOI: 10.1111/j.1439-0418.1998.tb01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Saturated hydrocarbons as kairomonal source for the egg parasitoid, Trichogramma chilonis Ishii (Hym., Trichogrammatidae)

Abstract: Studies on the effect of saturated hydrocarbons on parasitization by the egg parasitoid Trichogramma chilonis Ishii were carried out in the laboratory and net house. Bioassay of 11 hydrocarbons, viz. pentadecane, heptadecane, ecosane, heneicosane, docosane, tricosane, tetracosane, pentacosane, hexacosane, octacosane and hexatriacontane, were carried out under controlled conditions in the laboratory. These were also tested on potted maize plants in a net house. Among the saturated hydrocarbons, octacosane recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…Pentadecane showed the highest PAI at C 2 whereas the highest parasitism was noted at C 5 . P admavathi and P aul (1998) reported that 125 ng/cm 2 concentration of tetracosane and 250 ng/cm 2 concentration of eicosane recorded the highest response of Trichogramma chilonis (Ishii) which corroborates the present finding in the case of T. exiguum . They also reported that 62.5 ng/cm 2 concentration of octacosane and docosane, 125 ng/cm 2 concentration of pentacosane and 250 ng/cm 2 concentration of heneicosane recorded the highest responses of T. chilonis , which differ from the present findings.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Pentadecane showed the highest PAI at C 2 whereas the highest parasitism was noted at C 5 . P admavathi and P aul (1998) reported that 125 ng/cm 2 concentration of tetracosane and 250 ng/cm 2 concentration of eicosane recorded the highest response of Trichogramma chilonis (Ishii) which corroborates the present finding in the case of T. exiguum . They also reported that 62.5 ng/cm 2 concentration of octacosane and docosane, 125 ng/cm 2 concentration of pentacosane and 250 ng/cm 2 concentration of heneicosane recorded the highest responses of T. chilonis , which differ from the present findings.…”
Section: Resultssupporting
confidence: 90%
“…(1997), reported the highest parasitism by T. brasiliensis and Trichogramma japonicum (Ashmead) in the case of tricosane‐treated egg cards followed by pentacosane. P admavathi and P aul (1998) also reported tricosane to be the best hydrocarbon for attracting T. chilonis followed by octacosane and docosane. All these reports corroborate the present findings.…”
Section: 12 Parasitismmentioning
confidence: 95%
See 1 more Smart Citation
“…Octacosane recorded the highest parasitoid activity index followed by docosane and tricosane. However, the tricosane caused the highest percentage of parasitisation, which was at par with octacosane and docosane (Padmavathi and Paul 1998 ). Similar studies with the maize weevil, Sitophilus zeamais , an economically important pest of stored grains in tropical and subtropical regions of the world, also demonstrated the role played by VOCs from the maize ( Zea mays ) plants in host location by this insect.…”
Section: Modifi Cation Of Plant Volatilementioning
confidence: 53%
“…In social Hymenoptera, the cuticular lipids used in insect/insect relationships are mainly hydrocarbons and are involved in a variety of functions such as nest-mate recognition, reproduction, or parasitism (Dettner & Liepert 1994;Turillazzi et al 2000;Ruther et al 2002;Dani et al 2005). In parasitoid wasps, non-volatile host cuticular lipids are used in very short range and in specialist parasitoids serve as chemical recognition signals to identify host species (Vinson 1976;Rutledge 1996;Howard et al 1998;Padmavathi & Paul 1998;Kumazaki et al 2000) or to discriminate suitable individuals for oviposition (Vinson & Guillot 1972;Buckner & Jones 2005).…”
Section: Introductionmentioning
confidence: 99%